The role of endoscopic ultrasound in children with Pancreatobiliary and gastrointestinal disorders: a single center series and review of the literature - Alessandro Fugazza; Barbara Bizzarri; Federica Gaiani; Marco Manfredi; Alessia Ghiselli; Pellegrino Crafa; Maria Clotilde Carra; Nicola de'Angelis; Gian Luigi de'Angelis (BMC, 2017)
Abstract Background The role of endoscopic ultrasound (EUS) in the management of pancreatobiliary and digestive diseases is well established in adults, but it remains limited in children. The aim of this study was to evaluate the feasibility, safety, and clinical impact of EUS use in children. Methods This is a retrospective analysis of a prospectively acquired database of consecutive pediatric (< 18 years) patients presenting an indication for EUS for pancreatobiliary and gastrointestinal disorders. Results Between January 2010 and January 2016, 47 procedures were performed in 40 children (mean age of 15.1 ± 4.7 years; range 3-18). The majority of EUS (n = 32; 68.1%) were performed for pancreatobiliary and upper gastrointestinal pathologies, including suspected common bile duct stones (CBDs), acute biliary pancreatitis, recurrent/chronic pancreatitis, cystic pancreatic mass, recurrent hypoglycemia, duodenal polyp, gastric submucosal lesion, and perigastric abscess. In only 2 out of 18 children with suspected CBDs or acute biliary pancreatitis, EUS confirmed CBDs. EUS-guided fine needle aspiration was performed in 3 (6.4%) patients. Fifteen (31.9%) procedures were performed for lower gastrointestinal tract disorders, including suspected anal Crohn's disease, fecal incontinence, and encopresis. Overall, EUS had a significant impact on the subsequent clinical management in 87.2% of patients. Conclusion The present findings were consistent with results observed in the current relevant literature and support EUS as a safe and feasible diagnostic and therapeutic tool, which yields a significant clinical impact in children with pancreatobiliary and gastrointestinal disorders.